Association between anticholinergic activity and xerostomia and/ or xerophthalmia in the elderly: systematic review - E. Prado-Mel; P. Ciudad-Gutiérrez; H. Rodríguez-Ramallo; S. Sánchez-Fidalgo; B. Santos-Ramos; A. M. Villalba-Moreno (BMC, 2022)
Abstract Purpose The aim of this work was to investigate the association between anticholinergic burden or anticholinergic drug use and xerostomia and/or xerophtalmia in elderly through a systematic review of the published literature. Methods A search was carried out in 3 databases (CINAHL, Embase and Pubmed). Studies conducted in people ≥65 years of age, who took anticholinergic medications, and measured the association between the anticholinergic burden or the use of these medications with the prevalence of xerostomia and / or xerophthalmia, published up to August 2022, were selected. Studies published in languages other than Spanish and/or English were excluded. Results One thousand two hundred eleven articles were identified, 10 were selected for this review: six cross-sectional studies, two cohorts, one case-control and one randomized controlled clinical trial. A total of 3535 patients included in the different studies were studied. The most used scales were the Anticholinergic Drug Scale (ADS) and the Anticholinergic Risk Scale (ARS). Four articles studied the relationship between the use of anticholinergic medication and the prevalence of xerostomia and / or xerophthalmia, finding a positive relationship with xerostomia in all of them. Another 6 measured the relationship between anticholinergic burden and xerostomia and / or xerophthalmia. Four found a positive relationship between anticholinergic burden and xerostomia and/or xerophthalmia. Conclusions Our findings suggest a clear relationship between the use of anticholinergic drugs or anticholinergic burden and the presence of xerostomia. This relationship was less conclusive in the case of xerophthalmia.